Advances in Understanding Mating Type Gene Organization in the Mushroom-Forming Fungus Flammulina velutipes. Issue 11 (1st November 2016) - Wang, Wei; Lian, Lingdan; Xu, Ping; Chou, Tiansheng; Mukhtar, Irum; Osakina, Aron; Waqas, Muhammad; Chen, Bingzhi; Liu, Xinrui; Liu, Fang; Xie, Baogui; van Peer, Arend F
Abstract: The initiation of sexual development in the important edible and medicinal mushroom Flammulina velutipes is controlled by special genes at two different, independent, mating type (MAT) loci: HD and PR. We expanded our understanding of the F. velutipes mating type system by analyzing the MAT loci from a series of strains. The HD locus of F. velutipes houses homeodomain genes ( Hd genes) on two separated locations: sublocus HD-a and HD-b. The HD-b subloci contained strain-specific Hd1 / Hd2 gene pairs, and crosses between strains with different HD-b subloci indicated a role in mating. The function of the HD-a sublocus remained undecided. Many, but not all strains contained the same conserved Hd2 gene at the HD-a sublocus. The HD locus usually segregated as a whole, though we did detect one new HD locus with a HD-a sublocus from one parental strain, and a HD-b sublocus from the other. The PR locus of F. velutipes contained pheromone receptor ( STE3 ) and pheromone precursor ( Pp ) genes at two locations, sublocus PR-a and PR-b. PR-a and PR-b both contained sets of strain-specific STE3 and Pp genes, indicating a role in mating. PR-a and PR-b cosegregated in our experiments. However, the identification of additional strains with identical PR-a, yet different PR-b subloci, demonstrated that PR subloci can recombine within the PR locus. In conclusion, at least three of the four MAT subloci seem to participate in mating, and new HD and PR loci can be generated through intralocus recombination in F. velutipes .